Kajian Semiotika pada Video Musik di Udara - Efek Rumah Kaca dalam Konteks Politik - Fitri Andriani, Yunisa; Septian Rahman, Vicky (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
Injustice certainly occurs between communities, especially in politics. This injustice gave birth to activists who fought to defend the rights of the people who were victims of oppression, violence, kidnapping and so on. One of the human rights activists in Indonesia, Munir, who died because he was poisoned on his way to Amsterdam, Netherlands, became the inspiration for a music group called Efek Rumah Kaca on their song ‘Di Udara’. This pop genre song full of political messages conveyed to the community aims to inflame the spirit of activists and is expected to give birth to a new Munir. The political message packaged in the music video for the song ‘Di Udara’ is the focus of this research study. Through the study method all signs and codes contained in the visuals contained in this music video were analyzed using the sign theory namely Semiotics. The purpose of this study was to inflamethe spirit of activists and facilitate the delivery of activists’ messages through music videos.